Tadlis Digital: Membongkar Arsitektur Manipulasi Dark Pattern E-Commerce Perspektif Etika Bisnis Islam - Asep Koswara; Lina Herlina (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2026)
This study examines the phenomenon of dark patterns in e-commerce as a form of digital interface manipulation that unconsciously influences consumer behavior. The purpose of this research is to reconstruct dark pattern practices from the perspective of Islamic business ethics through the concept of tadlis. The method used is a qualitative approach based on library research with content analysis of literature on digital economics, consumer behavior, and Islamic jurisprudence. The findings show that dark patterns such as urgency manipulation, hidden costs, and scarcity cues create information asymmetry and encourage impulsive consumer decisions. This phenomenon can be reconstructed as a form of digital tadlis because it involves misleading information in transactions. The study confirms that such practices contradict the principles of honesty, justice, and mutual consent in Islamic business ethics. This research contributes conceptually by linking modern digital design with Islamic economic values and provides a foundation for developing more transparent and ethical e-commerce interface design.